JOB VACANCY DISCOURSE: Seeking an Opportunity for English Department Alumni in Newspapers - Budianto Hamuddin; Dahler - (Jurnal Ilmu Komunikasi, 2016)
This study aims to analyze the discourse of recent job vacancy ads in the newspaper and seeks for the opportunity of employment for the English departments’ alumni. This study also tries to iden- tify the highest frequently of job positions and requirements. The data collection based on 7.381 job vacancy ads during March- 2015 in 2 largest newspapers in Riau Province. Using Content analysis in discourse analysis area as the framework, this study reveals the different quantities of ads found both in teaching and non-teaching category offered an opportunity for the alumni. This study indicates an opportunity for the English departments’ alumni in a non-teaching category (33.9%) and teach- ing category (3.03%) from the total JV ads. This study also found the highest frequently of positions offered as English teachers in several institutions and non-teaching categories and the 10 highest frequently requirements to apply for the positions.